Analysis of Pedestrian Circulation Comfort at the Great Mosque of Central Java - Sepli Yandri; Silaban, Yessy Christanti (Institut Teknologi dan Bisnis Ahmad Dahlan, 2025)
The Great Mosque of Central Java, in Semarang is one of the most well known places of worship and religious tourism destinations, attracting many visitors for both prayer and the enjoyment of its beauty. This study aims to analyze the comfort of pedestrian circulation within the Great Mosque of Central Java, particularly focusing on the path leading to the main prayer room. The research examines the impact of circulation patterns on visitor activities and how vehicle parking influences pedestrian movement around the mosque. Additionally, climate factors such as temperature, humidity, and solar radiation play a role in determining visitor comfort when entering the mosque. This study provides an overview of how these factors contribute to the thermal comfort of visitors in the mosque area.